Cornus mas and Cornus Officinalis—Analogies and Differences of Two Medicinal Plants Traditionally Used - Czerwińska, Monika E.; Melzig, Matthias F. (Frontiers in Pharmacology, 2018)
Among 65 species belonging to the genus Cornus only two, Cornus mas L. and Cornus officinalis Sieb. et Zucc. (Cornaceae), have been traditionally used since ancient times. Cornus mas (cornelian cherry) is native to southern Europe and southwest Asia, whereas C. officinalis (Asiatic dogwood, cornel dogwood) is a deciduous tree distributed in eastern Asia, mainly in China, as well as Korea and Japan. Based on the different geographic distribution of the closely related species but clearly distinct plants, the ethnopharmacological use of C. mas and C. officinalis seems to be independently originated. Many reports on the quality of C. mas fruits were performed due to their value as edible fruits, and few reports compared their physicochemical properties with other edible fruits. However, the detailed phytochemical profiles of C. mas and C. officinalis, in particular fruits, have never been compared. The aim of this review was highlighting the similarities and differences of phytochemicals found in fruits of C. mas and C. officinalis in relation to their biological effects as well as compare the therapeutic use of fruits from both traditional plants. The fruits of C. mas and C. officinalis are characterized by the presence of secondary metabolites, in particular iridoids, anthocyanins, phenolic acids and flavonoids. However, much more not widely known iridoids, such as morroniside, as well as tannins were detected particularly in fruits of C. officinalis. The referred studies of biological activity of both species indicate their antidiabetic and hepatoprotective properties. Based on the available reports antihyperlipidemic and anticoagulant activity seems to be unique for extracts of C. mas fruits, whereas antiosteoporotic and immunomodulatory activities were assigned to preparations of C. officinalis fruits. In conclusion, the comparison of phytochemical composition of fruits from both species revealed a wide range of similarities as well as some constituents unique for cornelian cherry or Asiatic dogwood. Thus, these phytochemicals are considered the important factor determining the biological activity and justifying the use of C. mas and C. officinalis in the traditional European and Asiatic medicine.